Preemptive scheduling of jobs with agreeable due dates on a single machine to minimize total tardiness - Tian, Zhongjun; Ng, C.T.; Cheng, T.C.E. (Operations research letters, 2009)
We consider the problem of scheduling n preemptive jobs on a single machine to minimize total tardiness, subject to agreeable due dates, i.e., a later release date corresponds to a later due date. We prove that the problem is N P -hard in the ordinary sense by showing that it is N P -hard, and deriving a pseudo-polynomial algorithm for it.